Determinasi Decision Support System: Volume Sales, Marketing Distribution and Product Quality - Yahya, Surono; Ali, Hapzi (Green Publisher, 2023)
The Determination Decision Support System Literature Article: Effects of Sales Volume, Marketing Distribution and Product Quality is a scientific article that aims to build research hypotheses on the influence of variables to be used in further research, within the scope of Management Information Systems. The method of writing this Literature Review article is the library research method, which is sourced from online media such as Google Scholar, Mendeley and other academic online media. The results of this article are that: 1) Sales Volume influences the Decision Support System; 2) Marketing Distribution influences the Decision Support System; and 3) Product Quality influences the Decision Support System. Apart from these 3 exogenous variables that affect the endogenous Decision Support System variables, there are many other factors including price, promotion and market conditions.